Perancangan Sistem Pengaduan Berbasis Web di Kantor Balai Diklat Keagamaan Medan - Hafidz, Hasbanur; Yahya, Rafly Auliya (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2025)
This study aims to design and implement a web-based complaint system at the Medan Religious Training and Education Center as a solution to improve the effectiveness and efficiency of the complaint handling process. The problems encountered so far are that complaint management is still carried out manually, resulting in delays in response, lack of transparency, and potential data loss. The system development method used is the Unified Modeling Language (UML), with a focus on Use Case Diagrams and Activity Diagrams to model the complaint process flow in a structured manner. The system implementation was carried out using web-based technology, with black box testing as the testing method to ensure the system's functionality aligns with user needs. Testing results showed that all core system features, such as complaint registration, status tracking, and feedback provision, functioned according to specifications and produced valid outputs. With this system, the complaint process became faster, well-documented, and monitorable in real-time, thereby supporting improvements in public service quality within the relevant agency. This research provides practical contributions to the development of complaint management information systems and can serve as a reference for similar implementations in other government agencies.